Gatekeeping in professional higher education in Norway: ambivalence among academic staff and placement supervisors towards students with disabilities. Issue 6 (11th May 2020) - Langørgen, Eli; Kermit, Patrick; Magnus, Eva
ABSTRACT: Despite legislative regulations, many students with disabilities face barriers to their participation in higher education. In professional education, the requirements for placement practice add to the barriers for both students who need to disclose their impairments and request special arrangements, and staff who need to make the arrangements to accommodate to the students' special needs. The aim of this qualitative study was to explore the perspectives of academic staff and placement supervisors on supporting students with disabilities in professional programmes within health care, social work and teaching. Data were generated from focus group discussions with 13 lecturers who worked with students on campus, and 8 professionals who supervised students during practice placement. The results indicate an ambivalence among the staff and supervisors regarding working with students with disabilities. This ambivalence seems to be triggered by conflicting roles and values, unclear outcome measures to evaluate the students, a lack of knowledge of how to accommodate, time constraints, insufficient institutional support, as well as a lack of openness regarding students with disabilities in professional courses. The results call for an increased awareness of how complex processes in the structural and cultural environments affect students' disclosure of disability and the collaboration between the stakeholders.